1996
DOI: 10.1152/ajpheart.1996.270.3.h1085
|View full text |Cite
|
Sign up to set email alerts
|

Regional cerebral blood flow response to vibrissal stimulation in mice lacking type I NOS gene expression

Abstract: The role of nitric oxide (NO) in cerebral blood flow-metabolism coupling was assessed in SV-129 wild-type (WT) and neuronal (type I) NO synthase (NOS) knockout mice (Kn). Regional cerebral blood flow (rCBF; laser-Doppler flowmetry) was measured over the contralateral cortical barrel field during unilateral mechanical vibrissal deflection (2-3 Hz, 60 s) under urethan anesthesia. The rCBF response was similar in WT and Kn and did not differ when recorded over the intact skull or closed cranial window preparation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
79
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 12 publications
11
79
1
Order By: Relevance
“…NO is basically produced by 3 main enzymes: iNOS, eNOS and nNOS [38]. eNOS has primarily been held responsible for cerebellar artery basal tonus [39], and another study showed that there was ET-1 release in the normal cerebral endothelium [40]. In our study, while the brain eNOS expression levels in the diabetic groups decreased, the ET-1 expression levels were found to be increased.…”
Section: Discussionsupporting
confidence: 45%
“…NO is basically produced by 3 main enzymes: iNOS, eNOS and nNOS [38]. eNOS has primarily been held responsible for cerebellar artery basal tonus [39], and another study showed that there was ET-1 release in the normal cerebral endothelium [40]. In our study, while the brain eNOS expression levels in the diabetic groups decreased, the ET-1 expression levels were found to be increased.…”
Section: Discussionsupporting
confidence: 45%
“…Our study did not measure simultaneously changes in rCBF, which should be done in future experiments. The post-stimulus undershoot of rCBF occurs only in a minority of subjects, is highly variable (Irikura et al, 1994;Ma et al, 1996), task-dependent (Hoge et al, 1999), and can even be explained as an artifact of delayed rCBV changes (Mandeville et al, 1999). Furthermore, the ratio between post-stimulus and stimulus changes of rCBF, as calculated from these studies, reaches only values between approximately 0.15 and 0.3 (Hoge et al 1999;Irikura et al, 1994;Ma et al, 1996).…”
Section: Discussionmentioning
confidence: 71%
“…Future studies should determine how DNA damage responses in astrocytes alter the synthesis/release of these mediators. There is also strong experimental evidence that endothelial NO production contributes to glio-vascular coupling (Chen et al 2014;Girouard et al 2007;Longden and Nelson 2011;Ma et al 1996;Stobart et al 2013; Toth e t a l . 2 0 1 5 b ) .…”
Section: Discussionmentioning
confidence: 99%